The Connection of Thought, Culture and Language: Revoking Myth Unveiling Truth: Keterkaitan antara Pikir, Budaya dan Bahasa: Menyingkap Mitos Mengungkap Kebenaran - Khairuddin, Khairuddin (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2021)
Scholars and laymen alike are interested in understanding how thought, culture and language are related. Misunderstanding of this relatedness may have serious consequences: legislators make misleading constitutions, judges impose wrong legal rulings and imprisonment on the innocent, and educators apply ineffective pedagogy. Relativism and mentalism, the two leading linguistic schools of thought, have been around in sharp differences explaining about the relation between thought, culture and language. Relativism believes that language precedes, determines, and influence or shapes though, whereas mentalism hypothesizes the contrary that it is thought that creates and changes language. This article describes the theoretical concepts and empirical proofs underlying the two views of linguistic views. By using literature comparative analysis, this study has found that mentalism has strong standpoints in comparison with relativism’s which have weak standpoints. This study also presents implications for language learning that are rooted in the mentalism conception.